Hyperelongated biglycan: the surreptitious initiator of atherosclerosis - Little, Peter J; Osman, Narin; O'Brien, Kevin D (Current opinion in lipidology, 2008)
To outline a role for the dermatan sulfate proteoglycan biglycan and specifically its growth factor modified form having elongated glycosaminoglycan chains as being a primary initiator of atherosclerosis. Antiatherosclerotic therapies have mostly targeted epidemiologically identified, experimentally confirmed risk factors. The efficacy of such therapies is less than optimal, and rates of cardiovascular disease remain stubbornly high. A variety of targets have been actively pursued, but as yet no new therapy has emerged that specifically targets the vessel wall. One area concerns the role of proteoglycans in the trapping of atherogenic lipoproteins as an early and initiating step in atherogenesis. On the basis of studies in human coronary arteries, the prime proteoglycan for lipoprotein retention is biglycan. The glycosaminoglycan chains on biglycan are subject to regulation that yields several structural changes, but most prominently elongation of the chains to form 'hyperelongated biglycan'. Multiple animal studies and a recent human disorder study have demonstrated the colocalization of atherogenic lipoproteins with biglycan in atherosclerotic lesions. Moreover, in the human atherosclerosis, the deposition of lipid appears to precede the chronic inflammatory response typical of atherosclerotic lesions. The process of biglycan-associated glycosaminoglycan elongation represents a novel potential therapeutic target worthy of full investigation for the prevention of atherosclerosis.